Rare complication after totally extraperitoneal endoscopic inguinal hernia repair: Small bowel perforation without peritoneal disruption. Issue 4 (10th May 2016) - Kojima, Shigehiro; Sakamoto, Tsuguo; Honda, Masayuki; Nishiguchi, Ryohei; Ogawa, Fumihiro
Abstract: We report a rare case of visceral injury after totally extraperitoneal endoscopic inguinal hernia repair. A 48‐year‐old man underwent needlescopic totally extraperitoneal repair of a direct inguinal hernia. Bleeding from a branch of the inferior epigastric vessels occurred at the beginning of the extraperitoneal dissection with a monopolar electrosurgical device. Hemostasis was prolonged. However, herniorrhaphy and mesh repair were successfully performed, and no peritoneal disruption or pneumoperitoneum was visible. The patient was discharged home on the next day. However, 30 h after this operation, he underwent diagnostic and operative laparoscopy because of acute abdominal pain. Ileal perforation was found and repaired, and pathological examination indicated cautery artifact. Thus, thermal damage to the ileum during the initial operation may have caused the bowel perforation. To the best of our knowledge, no other cases of bowel perforation after totally extraperitoneal repair without peritoneal disruption have been reported.